Effectiveness of Building Information Systems in Building Planning of Security Offices (Study at Padang Tualang Prefecture Office) - Ary Syardand; Februati Trimurni (Dinasti Research, 2024)
The rapid development of information and communication technology provides opportunities for the government to access, manage and use information quickly and accurately in regional development efforts. Law 32 of 2004 concerning Regional Government underlines the importance of effective resource management. This research highlights the role of the Regional Government Information System (SIPD) in development planning in Padang Tualang District. Based on Permendagri No.70 of 2019, SIPD functions to synchronize development plans with the budget. This study evaluates the effectiveness of SIPD by measuring goal achievement, efficiency, integration, and adaptation. The results show that the implementation of SIPD in Padang Tualang still faces several obstacles, including delays in data input and lack of data integration with district/city governments. However, SIPD also offers several advantages such as more structured data input and easy access by the public. This research provides a descriptive view of the effectiveness of SIPD in regional development planning and suggests improving the quality of human resources and supporting infrastructure to maximize the benefits of SIPD.